Trend analysis with the annual temperature and precipitation in the Izmir district of Turkey - Mersin, Denizhan; Tayfur, Gökmen; Vaheddoost, Babak; Safari, Mir Jafar Sadegh (My University, 2022)
The effects of climate change on the water resources of the Aegean Region in Turkey are investigated through trend analysis of yearly temperature (daily average) and total precipitation time series data gathered from 3 stations (Izmir, Seferihisar, Cesme) in the research region. The techniques of Sen, Mann-Kendall, and Spearman's rho test are employed to identify historical patterns in the area. Theil-Sen technique is used to identify the change point(s) in the time series, while the Pettitt test is used to determine the size of the slope in the time series. Results show statistically significant trends of an increasing character in the temperature and precipitation time series at the chosen station. The rate of rise in precipitation and temperature was determined using the Theil-Sen test to be 7.3-7.9 mm/year and 0.20-0.3 °C/decade, respectively. Additionally, it was found that 1998 was the year for all sites where the change points in the temperature trends identified by the Pettitt test occurred. By taking into account the findings, a framework to boost climate change resilience will be required since the scale of severe occurrences will alter in the future.
Bildiri - Yayımlanmış
Keywords: Environment; Hydraulics; Hydrology; Hydrometeorology; Precipitation; Civil engineering